Теоретическое и экспериментальное сравнение алгоритмов векторного управления асинхронным двигателем без измерения токов статора - Пересада, Сергей Михайлович; Алисов, Андрей Сергеевич (НТУ "ХПИ", 2010)
Theoretical and experimental comparison of vector control algorithms for induction motors without stator current measurements is presented. Current sensorless speed-flux tracking control algorithm guarantees global asymptotic flux/speed tracking with asymptotic decoupling of mechanical and electromagnetic subsystem achieving at the same time asymptotic field orientation. Results of simulation and experimental tests illustrate that increasing of speed controller proportional gain in «V-type» algorithm results to performances degradation, while current sensorless speed-flux tracking control algorithm provide high tracking features.
Theoretical and experimental comparison of vector control algorithms for induction motor without stator current measurements
Keywords: скорость угловая; регулятор; электропривод